Quality of life, coping, and psychological and physical symptoms after surgery for non-metastatic digestive tract cancer - Calderón, Caterina; Jiménez-Fonseca, Paula; Hernández, Raquel; Mar Muñoz, María del; Mut, Margarida; Mangas-Izquierdo, Montserrat; Vicente, M Ángeles; Ramchandani, Avinash; Carmona-Bayonas, Alberto (Surgical oncology, 2019)
The aim of this study was to investigate the impact of curative surgery for non-metastatic digestive tract cancers on quality of life (QoL), psychological status, and coping strategies. A prospective, transversal, multicenter study was conducted in 404 patients: 361 with colorectal, 44 with gastroesophageal, and 35 with pancreaticobiliary cancer six months after surgery. Participants completed questionnaires evaluating QoL, including functioning (EORTC-QLC-C30), coping strategies (Mini-MAC), and psychological distress (BSI-18). The effects of surgery had a strong impact on functional domains, global QoL, and symptoms, especially in pancreaticobiliary and gastroesophageal cancer. Patients with pancreaticobiliary and gastroesophageal cancer had lower functional scale scores than those with colorectal cancer. Fatigue, appetite loss, diarrhea, depression, and psychological distress were the most common symptoms after surgery. Subjects with pancreaticobiliary cancer reported more fatigue, pain, insomnia, depression, somatization and psychological distress, whereas individuals with gastroesophageal cancer exhibited more fatigue, nausea/vomiting, diarrhea, depression, psychological distress, and helplessness than those with colorectal cancer. Only participants with colorectal cancer displayed improved QoL six months post-surgery, albeit their psychological state had worsened. Surgeons should discuss expectations regarding symptoms and QoL with patients prior to surgery to minimize physical and psychological impact. •Surgery for non-metastatic digestive cancers is the only curative treatment.•The effects of surgery had a negative impact on the health-related quality of life (QoL) in cancer patients.•Fatigue, appetite loss, diarrhea, depression, and psychological distress were the most common symptoms after surgery.•Surgeons should discuss expectations regarding symptoms and QoL with patients prior to surgery to minimize impact.